An assessment of thermal impact on chemical characteristics of edible oils by using FTIR spectroscopy - Soni, A. (Elsevier Ltd, 2022)
The utilization of degraded edibles oils as an abrasive media was considered as one of the effective to reduce the requirement of fresh abrasive flow media in Abrasive Flow Machining (AFM). FTIR spectroscopy was identified as an effective tool to characterize and identify the structure of organic molecules. In the present study, an analysis for the change in chemical compositions fresh and used edible oils due to thermal effect using Fourier Transform Infrared (FTIR) spectroscopic method was carried out. The study aims to analyze the deterioration of edible oils, namely palm and mustard oil, by identifying the different constituents present in the oil. The study finds the chemical composition of thermally degraded in palm and mustard oil. The infrared bands changing during heating in oil samples have been examined, and the result indicates a range of chemical transformations due to the reactions. The ranges of peak frequencies of the fresh mustard and palm oils were found to 3010â653 cmâ1 and 2931â1745 cmâ1, respectively. After the first heating at 170â230 Â°C the ranges of peak frequencies of the fresh mustard and palm oils shifted to 2923â677 cmâ1 and 2921â722 cmâ1 respectively. Moreover, the study showed the potential of FTIR spectroscopy for compositional analysis of edible oils for the application of AFM media. Â© 2022